Iminosugar-based ceramide mimicry for the design of new CERT START domain ligands. Issue 6 (15th March 2017) - Santos, Cécile; Stauffert, Fabien; Ballereau, Stéphanie; Dehoux, Cécile; Rodriguez, Frédéric; Bodlenner, Anne; Compain, Philippe; Génisson, Yves
Graphical abstract: Abstract: The enigmatical dichotomy between the two CERT/GPBP protein isoforms, their vast panel of biological implications and the scarcity of known antagonist series call for new ligand chemotypes identification. We report the design of iminosugar-based ceramide mimics for the development of new START domain ligands potentially targeting either protein isoforms. Strategic choice of (i) an iminoxylitol core structure and (ii) the positioning of two dodecyl residues led to an extent of protein binding comparable to that of the natural cargo lipid ceramide or the archetypical inhibitor HPA-12. Molecular docking study evidenced a possible mode of protein binding fully coherent with the one observed in crystalline co-structures of known ligands. The present study thus paves the way for cellular CERT inhibition studies en route to the development of pharmacological tools aiming at deciphering the respective function and therapeutic potential of the two CERT/GPBP protein isoforms.